Factors Affecting the Utilization of Antenatal Care Visit in Nepal (Patan Pragya, 2019)
The antenatal care is an entry point for maternal and child health care service utilization through which pregnancy risk can be detected and managed and contributes to reducing both the maternal and neonatal mortality. This study is an attempt to identify the factors affecting on the utilization of antenatal care in Nepal. It is based on data of Nepal Demographic and Health Survey (2016) that covered 3,998 currently married women, aged 15-49 years who had a live birth in the 5 years preceding the survey. In this study, ANC visit is dependent variables is defined by women who attend ANC as 4 or more visits and the women who attend ANC as less than 4 times visits. Information on socio-demography characteristics and the utilization of antenatal care (ANC) visits are collected. Findings of this study show that different demographic, socio-economic factors are responsible for the utilization of antenatal care services in Nepal. Despite the need and the efforts made by the government of Nepal through different policies to improve access to antenatal care service, complete ANC utilization has been inadequate.